Wild By Design Strategies for Creating Life-Enhancing Landscapes - Ruddick, Margie; SpringerLink (Online service) (Washington, DC : Island Press/Center for Resource Economics : Imprint: Island Press, 2016)
Can nature$1 (Bin all its unruly wildness$1 (Bbe an integral part of creative landscape design? In her beautifully illustrated book, Wild by Design, award-winning designer Margie Ruddick urges designers to look beyond the rules often imposed by both landscaping convention and sustainability checklists. Instead, she offers a set of principles for a more creative and intuitive approach that challenges the entrenched belief that natural processes cannot complement high-level landscape design. Wild by Design defines and explains the five fundamental strategies Ruddick employs, often in combination, to give life, beauty, and meaning to landscapes: Reinvention, Restoration, Conservation, Regeneration, and Expression. Drawing on her own projects$1 (Bfrom New York City$1 (Bs Queens Plaza, formerly a concrete jungle of traffic, to a desertscape backyard in Baja, California, to the Living Water Park in Chengdu, China$1 (Bshe offers guidance on creating beautiful, healthy landscapes that successfully reconnect people with larger natural systems. A revealing look into the approach of one of sustainable landscape design$1 (Bs most innovative practitioners, Wild by Design stretches the boundaries of landscape design, offering readers a set of broader, more flexible strategies and practical examples that allow for the unexpected exuberance of nature to be a welcome part of our gardens, parks, backyards, and cities.s
Acknowledgments -- Introduction -- 1. Reinvention -- 2. Restoration -- 3. Conservation -- 4. Regeneration -- 5. Expression -- Conclusion.
Keywords: Environment; Regional planning; Urban planning; Architecture; Landscape architecture; Graphic design; Sustainable development; Environment; Sustainable Development; Landscape/Regional and Urban Planning; Landscape Architecture; Cities, Countries, Regions; Interaction Design; Electronic books